1980
DOI: 10.1021/jo01313a001
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid catalyzed ene reactions of ethynyl p-tolyl sulfone

Abstract: Ethynyl ,D-tolyl sulfone undergoes EtAlC12-catalyzed ene reactions with alkenes to give 1,4dienyl p-tolyl sulfones in good yield.We have recently described the Lewis acid catalyzed ene and [2 + 21 cycloaddition reactions of ethynyl esters and ketones with alkene^.^^^ Depending on the substitution pattern of the alkene, good yields of ene adducts and/or cyclobutenes are obtained at 25 "C. The adducts which result from these reactions have been used for the syntheses of the A1 component of the female sex pheromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Acetylenic sulfones are also known to undergo Lewis acid-catalyzed ene reactions. 2m, We observed that the treatment of β-pinene with 1 afforded the ene reaction product 23 in the absence of a Lewis acid, as shown in Scheme . Only the one regioisomer, tentatively identified by NOE experiments and by the chemical shift of the olefinic proton of the β-(phenylseleno)vinyl sulfone moiety, was isolated.…”
Section: Resultsmentioning
confidence: 98%
“…Acetylenic sulfones are also known to undergo Lewis acid-catalyzed ene reactions. 2m, We observed that the treatment of β-pinene with 1 afforded the ene reaction product 23 in the absence of a Lewis acid, as shown in Scheme . Only the one regioisomer, tentatively identified by NOE experiments and by the chemical shift of the olefinic proton of the β-(phenylseleno)vinyl sulfone moiety, was isolated.…”
Section: Resultsmentioning
confidence: 98%
“…This compound (1.0 g) in ethanol (20 ml) was treated with potassium hydroxide (0.3 g) when a precipitate formed immediately. The mixture was stirred for 30 min after which water (50 mi) was added and most of the ethanol evaporated off; extraction of the residue with ether and distillation yielded the title compound (10) (20), 175 (25), 148 (loo), and 147 (50).…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogen peroxide and m‐ chloroperoxybenzoic acid ( m‐ CPBA) are commonly used oxidizing agents in this technique. Currently, these two oxidizing reagents remain the most used for this purpose (Scheme ) . Peroxybenzoic acid and peroxyethanoic acid have also been used for this purpose, although to a lesser extent.…”
Section: Oxidation Of Alkynyl Sulfides With Peroxidesmentioning
confidence: 99%